Pengaruh Penggunaan AI (Chatbot) terhadap Pemerolehan Bahasa Kedua Mahasiswa di STAIN Mandailing Natal - Nur Fadilah (PT. Willy Print Art, 2025)
This research examines the influence of using artificial intelligence (AI) powered chatbots on second language acquisition among university students. Chatbots hold potential as interactive and personalized language learning tools. Data was collected from students using chatbots in their second language learning process and analyzed to understand the effectiveness of chatbots in improving language skills. The findings are expected to provide insights into the utilization of this technology in language learning contexts. The implications of this research can serve as a foundation for the development and implementation of chatbots as innovative and effective language learning aids.